СИСТЕМА ЗЛОЧИНІВ ПРОТИ ДЕРЖАВНОГО СУВЕРЕНІТЕТУ І ТЕРИТОРІАЛЬНОЇ ЦІЛІСНОСТІ УКРАЇНИ - Носач, Андрій Володимирович (SUPREMANCE OF LAW, 2019)
The article is devoted to the analysis of certain problematic issues of crime that affects the state sovereignty and territorial integrity of Ukraine. The purpose of the article is to carry out an analysis of the system ofcrimes against state sovereignty and territorial integrity of Ukraine as the basis ofcrime in this area. In the framework of scientific research and to achieve the goal, put forward a number of priority tasks, namely: to find out the essence of the content of the concept of «system of crimes»; determine the place of the crime system within the criminological characteristics ofcrime; as well as outline the system ofcrimes against state sovereignty and territorial integrity of Ukraine and analyze it for the subject of correlation with crime in this area. After analyzing the concept of «system» and «crime» it is noted that under the system of crimes means the multiplicity of interrelated socially dangerous acts, that is, crimes that form a single whole, interact with the external environment and between themselves, and have a single purpose. Based on the concept ofcrime, it is noted that the prediction of the existence of a system ofcrime is one of the signs of crime. At the same time, the system ofcrimes, along with understanding of it as a sign ofcrime, at the same time, serves as the basis for the formation of the structure of this crime. The system of crimes encroaching upon state sovereignty and territorial integrity of Ukraine form the following socially dangerous acts: - an attack on the territorial integrity and inviolability of Ukraine (Article 110 of the Criminal Code of Ukraine); - financing of actions committed for the purpose of violent change or overthrow of the constitutional order or seizure of state power, changes in the boundaries of the territory or the state border of Ukraine (Article 110-2 of the Criminal Code of Ukraine); - state treason (Article 111 of the Criminal Code of Ukraine). It is emphasized that state sovereignty and territorial integrity of Ukraine act as a system-forming components of crime in this sphere, and the system of crimes against state sovereignty and territorial integrity of Ukraine is considered as the basis of this crime in the form of its structure.